“Madre Fronteriza”: Estudo conjunto de prevalência de sífilis,tricomoníase e HIV em gestantesda tríplice fronteira do Alto do Rio Solimões - Benzaken, Adele S.; García, Enrique G.; Rodrigues, Adelma de O.; Mora, Claudia; Sánchez, Martín S.; Sardinha, José Carlos G. (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: the epidemiologists of STIs are poorly defined in the isolated frontier regions of the Amazon. Objective: With the goal of deepening the knowledge and of stimulating neighbor countries to practice shared interventions, a study of prevalence was founded with the resources of its own area of interest. Method: such study took place with samples from pregnant women from each region of the Upper Solimões River. This area comprehends eight municipalities in the northwest of the International Amazon, which are found in the triple border of Brazil, Colombia, and Peru. At the end of the study (08/03/03 – 11/04/03), a total number of samples from 550 women had been incorporated to a starting number of only 338. An epidemiological inquiry was applied and samples were collected for the study of vaginal trichomoniasis, syphilis, and HIV. Result: the level of prevalence found for the three investigated STIs were of 7,4%, more aggravated in the Peruvian side which was superior to 10%. The prevalence for vaginal trichomoniasis, syphilis, and HIV infection was respectively of 6,3%, 0,92%, and 0,2%. There were slight differences between different residential communities and countries that integrated the study. Conclusion: it is very likely that the curable STIs represent an important health problem. Joint controlling measures should be implemented so to avoid a fast dissemination of the HIV/Aids epidemic, which is found at this moment in a premature developing stage. This study has showed that the cooperation between neighbor countries is attainable in the control of STIs.